2022
DOI: 10.4102/hsag.v27i0.1880
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the psychosocial challenges faced by pregnant teenagers in Ditsobotla subdistrict

Abstract: This study explores and describes the psychosocial challenges faced by pregnant teenagers in the Ditsobotla subdistrict. Setting:The study was conducted in three health centres in the Ditsobotla subdistrict.Methods: A qualitative-exploratory-descriptive and contextual research design was used. Non-probability purposive and convenience sampling techniques were used to select the participants. Semistructured individual interviews through WhatsApp video calls were used to collect data, which were analysed using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…The findings reveal that these teenagers experience mental problems, specifically depression and stress, as most of them find themselves worrying about many things during their pregnancy or parenting journey. This is consistent with the findings of other studies that pregnancy poses a serious challenge to the mental health of pregnant and parenting adolescents [22][23][24][25]. In addition, adolescents indicated that the contributing factors to most of their worries include problems with their families and friends related to support and acceptance of their pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…The findings reveal that these teenagers experience mental problems, specifically depression and stress, as most of them find themselves worrying about many things during their pregnancy or parenting journey. This is consistent with the findings of other studies that pregnancy poses a serious challenge to the mental health of pregnant and parenting adolescents [22][23][24][25]. In addition, adolescents indicated that the contributing factors to most of their worries include problems with their families and friends related to support and acceptance of their pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Pregnant adolescents often experience psychosocial challenges, such as a great deal of stress when dealing with an unwanted pregnancy, lack of preparation for parenthood, lack of income, and birth complications-complicated by the stigma from their families, friends, and community. Unaddressed psychosocial challenges during adolescent pregnancy can negatively affect health outcomes for both mother and child [18].…”
Section: Discussionmentioning
confidence: 99%
“…According to Ntshayintshayi et al (2022), pregnant teenagers felt that they disappointed their families and society. Pregnant teenagers and their families, school, and community recognize the consequences of early childbearing as a social deficiency.…”
Section: Young Mothers' Experiences In Early Parenthoodmentioning
confidence: 99%
“…Some even use provocative words. Due to early pregnancy, pregnant adolescents encounter stigmatization, rejection, social exclusion, and mockery from their families, peers, and community (Ntshayintshayi et al, 2022).…”
Section: Young Mothers' Experiences In Early Parenthoodmentioning
confidence: 99%
See 1 more Smart Citation